ANALISIS KINERJA BUMDES SYARIAH KEMBANG SETANJUNG DALAM PEMBERDAYAAN EKONOMI MASYARAKAT - Ari Wibowo (Fakultas Ekonomi Universitas Pasir Pengaraian, 2023)
Rural economic institutions which are one of the community empowerment strategies are still an important part of the village community, but the positive influence felt by the village community itself is still lacking. Community empowerment is one method of poverty alleviation by maximizing local communities in their work so that they will achieve the ultimate goal of community welfare. The purpose of this study was to determine the performance of the Syariah Kembang Setanjung Village Owned Enterprise (BUMDes) in Tanjung Medan Village, North Tambusai District, Rokan Hulu Regency in terms of service, profit and sustainability aspects. The research approach used is a qualitative approach. The primary data sources are the Village Head, Village Treasurer, BUMDes Director, BUMDes secretary, and local community leaders. While secondary data include: data in the form of reports, documents, raw data and necessary data. The data collection instruments used in this study were interviews, observation and documentation studies. The data analysis method in this study collects data, reduces data, presents data and draws conclusions. The results showed that the performance of the Syariah Kembang Setanjung Village Owned Enterprise (BUMDes) Tanjung Medan Village, North Tambusai District, Rokan Hulu Regency in terms of service, profit, and sustainability aspects showed that BUMDes managers had been able to serve the community well and the community felt they had benefited from their existence. ease of terms, interest, and a simpler and easier BUMDes installment system that has an impact on community economic empowerment.